√(- 9 ) / (( 4 - 7 i ) - ( 6 - 6 i )) = 3 i / ( 4 - 7 i - 6 + 6 i ) =
= 3 i / ( - 2 - i ) = - 3 i / ( 2 + i ) =
![= \frac{-3i}{2 + i}* \frac{2 - i}{2 - i}= \\ = \frac{-6i+3i ^{2} }{2- i^{2} }= \\ = \frac{-3-6i}{2+1}= \frac{-3-6i}{3}=](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B-3i%7D%7B2%20%2B%20i%7D%2A%20%5Cfrac%7B2%20-%20i%7D%7B2%20-%20i%7D%3D%20%5C%5C%20%3D%20%20%20%5Cfrac%7B-6i%2B3i%20%5E%7B2%7D%20%7D%7B2-%20i%5E%7B2%7D%20%7D%3D%20%5C%5C%20%3D%20%5Cfrac%7B-3-6i%7D%7B2%2B1%7D%3D%20%5Cfrac%7B-3-6i%7D%7B3%7D%3D%20%20%20)
=
- 1 - 2 i
Answer:
a = 2
b = 18
a/b = 1/9
Step-by-step explanation:
-5x•(2x^2+x+3) is the answer
Answer:
D
Step-by-step explanation:
the triangle has reflected across either x-axis or p-axis. If across x-axis, the triangle needs to translate left and then up (no option for this).
Step 1- Simplify brackets
c + 4 - 3c -2 = 0
Step 2- Simplify c + 4 - 3c -2 to -2c + 4 - 2
-2c + 4 - 2 = 0
Step 3- Simplify -2c + 4 - 2 to 2c + 2
-2c + 2 = 0
Step 4- Subtract 2 from both sides
-2c = -2
Step 5- Divide both sides by -2
Answer: c = 1